A local experience of non-operative management for an appendicitis cohort during COVID-19. (March 2021) - Mai, Dinh Van Chi; Sagar, Alex; Menon, Nainika Suresh; Claydon, Oliver; Park, Ji Young; Down, Billy; Keeler, Barrie David
Abstract: Background: During the first United Kingdom COVID-19 wave, the Royal Colleges of Surgeons initially recommended conservative management with antibiotics instead of surgery for appendicitis. This study compared local outcomes of appendicitis during this period with a pre-COVID-19 cohort. Methods: An observational study was conducted in a district general hospital. All episodes of appendicitis were prospectively studied from 25 th March 2020 until 26 th May 2020 and compared with a retrospective pre-COVID cohort from 27 th November 2019 until 29 th January 2020. Primary outcome was 30-day treatment failure of simple appendicitis for conservatively managed cases during COVID-19 compared to surgically managed cases pre-pandemic. Treatment failure was defined as any unplanned radiological or surgical intervention. Results: Over nine weeks, there were 39 cases of appendicitis during COVID-19 and 50 cases pre-COVID-19. Twenty-six and 50 cases underwent appendicectomy during and pre-COVID-19 respectively. There was no difference in 30-day postoperative complication rates and nor were there any peri-operative COVID-19 infections. Twelve cases of simple appendicitis underwent conservative management during COVID-19 and were compared with 23 operatively managed simple cases pre-pandemic. There was a higher failure rate in the conservative versus operative group (33.3 vs 0% OR = 24.88, 95% CI 1.21 to 512.9, p=0.0095 ). Length of stay was similar (1.5 vs 2.0 p=0.576 ). Discussion: Locally, conservative management was more likely to fail than initial appendicectomy. We suggest that surgery should remain first line for appendicitis, with conservative management reserved for those with suspected or proven COVID-19 infection. Highlights: A single UK centre experience of appendicitis during the first COVID-19 wave. A higher failure rate in conservatively versus surgically managed appendicitis. However, those failing conservative management suffered no adverse events. Length of stay was similar for conservative versus surgically managed patients.